Comparison of long-term kidney functions after radical nephrectomy and simple nephrectomy - Olcucuoglu, Erkan; Tonyali, Senol; Tastemur, Sedat; Kasap, Yusuf; Sirin, Mehmet Emin; Gazel, Eymen; Olcucuoglu, Esin; Odabas, Oner; Ates, Can; Olcucu, Mahmut Taha (PeerJ, 2019)
Objective To determine if there is a difference in proceeding to CKD between patients who had undergone radical nephrectomy (RN) and simple nephrectomy (SN) for different indications by comparing the short- and long-term renal function. Materials and Methods We retrospectively analyzed the records of all patients who underwent nephrectomy (either for malign or benign indications) in our clinic between January 2007 and September 2017. The patients were divided into 2 groups according the type of surgery: 1) Radical nephrectomy Group, 2) Simple Nephrectomy Group. Renal function was evaluated with Glomerular Filtration Rate (GFR) calculated using the MDRD formula. Results A total of 276 patients were included in the study. There were 202 patients in RN Group and 74 patients in SN Group. The mean age of the patients in RN Group and SN Group were age 59,2 ± 11,5 and 49,9 ± 15,1 years, respectively (p = 0.001). GFR levels of patients in RN Group versus SN Group were as follows: Preoperative period: 84.9 vs. 81 mL/min/1.73 m2; postoperative 1st day: 60.5 vs. 84.4 mL/min/1.73 m2, postoperative 1st month 58.9 vs. 76 mL/min/1.73 m2, postoperative 1st year: 59.5 vs. 74.1 mL/min/1.73 m2; at last control 60.3 and 76.1 mL/min/1.73 m2. While preoperative GFR was found to be similar in two groups (p = 0.26), postoperative GFR values were found to be significantly lower in Group RN (p < 0.001). In comparison of the decrease in GFR in two groups at last follow-up, significantly higher decrease was observed in RN Group, 29% vs. 6%, (p < 0.05). Conclusion The decrease in GFR exists more common and intensive after RN compared to SN. In long-term, compensation mechanisms that develop after sudden nephron loss like radical nephrectomy deteriorates kidney function more than gradual nephron loss as in benign etiologies which indicates simple nephrectomy.
Keywords: Nephrectomy; Chronic Kidney Disease; GFR; Renal carcinoma